Annual Report 1993-94 - Planning Commission (Planning Commission Government of India, 1994)
The Planning Commission Annual Report 1993-94 provides a comprehensive review of India’s economic and developmental progress during the second year of the Eighth Five-Year Plan (1992-97). The report highlights economic consolidation with a GDP growth of 4.0%, improved agricultural output, and moderate industrial recovery. Key priorities included human development, with increased allocations for health, education, and welfare, alongside initiatives for employment generation and rural empowerment. The report emphasizes decentralisation through district-level and micro-level planning, addressing regional imbalances via targeted programmes such as Hill Area, Western Ghats, and Border Area Development. Infrastructure investment, public enterprise reform, and enhanced private sector participation were identified as critical for sustaining growth. The document also details strategic initiatives in planning, monitoring, and capacity building, underscoring the integration of grassroots participation with national objectives to promote equitable and sustainable development across India.
Government of India Planning Commission
Keywords: Planning Commission; Eighth Five-Year Plan; Annual Plan; Decentralisation; Human Development; Rural Development; Infrastructure; Employment Generation; Regional Imbalances; Public-Private Partnership